Lietuvos politinių partijų požiūris į Lenkiją 1920-1926 metais: nuo modus vivendi paieškų iki nuolatinės konfrontacijos - Grodis, Andrius (Lietuvos istorijos studijos, 2008)
In the end of the First World War, Lithuanian (having just regained independence) international position was badly complicated by a terror conflict with Poland with respect to Vilnius that took place in 1919. However, despite the hostility to Poland entrenched in society, the leaders of political parties who envisioned the greatest danger to the state's independence from Soviet Russia and Germany actively sought pacific means of resuming the historical capital of the state and for ways of friendly affiliation of interstate relations. Modus vivendi appropriate for Poland and Lithuania was sought with the mediation of the League of Nations and great Western states in 1921 by the leaders of governing Christian Democrats and Union of Peasants parties. They were in favour of the second variant of Hymans' project but only agreed to accept it on condition that the League of Nations would take into account the contra-suggestions of the Lithuanian Government which reduced Poland's influence in domestic life. Having approved the project, there were hopes not only to regain the capital, to start economic relations useful for both countries, but also to receive support from great Western states, which was vital for Lithuania as for other Baltic states in seeking protection from the eventual threat of Soviet Russia and Germany.The propagandistic campaign by the Lithuanian National Union and Social Democrats, which caused general tension in the country, as well as society's and the military's discontent with the Government and the governing political parties' inability to resist the pressure, reflected a lack of civic consciousness and inner political consolidation in the state taking its first steps in democracy.The political parties' goal to use the problem of the relationship with Poland in their fight and in such a way obtain as great support from society as possible, further reduced the possibilities to solve the interstate conflict. As the Copenhagen negotiations in the autumn of 1925 illustrated, the Christian Democrats' attempt to reduce the tension between the two small countries by starting economic relations of a narrow nature was met with strong hostility by the opposing Union of Peasants and National Union Parties, as well as by the majority of society supporting them. However, the attitude of the Christian Democrats that it was possible to launch economic relationships with Poland, and the Social Democrats' belief that it was even crucial to do so, which were regarded as a first step in resuming Vilnius, in fact reflected that the leaders of the parties had enough rational reasoning as well as a mature attitude to international relations.Unsuccessful attempts to regulate the conflict with Poland in a pacific way and to regain the historical capital made the leaders of the state's political parties choose a state of permanent confrontation with Poland and seek support to ensure the safe existence of the state from the Soviet Union and Germany.